Terahertz Spectroscopy and Imaging Detection of Defects in Civil Aircraft Composites - Mian Zhong; Bingwei Liu; Chen Li; Zhiqi Wang; Dongshan Wei; Bin Zhou; Xin Dai; Yajun Xu (Journal of Spectroscopy)
Composite materials have increasingly become a high proportion of the structural weight of aircraft due to their excellent performances. Different types of damages may occur in the aircraft service period, which will bring potential safety risks to aircrafts. To investigate the defect damage detection and its spectral characteristics and imaging of carbon-fiber-reinforced polymer composite laminates, defects from the low-velocity impact damage in composites were measured by the THz time-domain reflection imaging system. Results show that there exists obvious THz spectral differences between the impact damaged defects and nondefect. The effective detection frequency band for the low-speed impact damaged defect is 0.12–2.0 THz. In the time domain, there are attenuations and delays in the spectra of defects relative to those of nondefects. In the frequency domain, with the increase of frequency, the power spectral density of the defect first increases and then decreases, and the absorption coefficient increases slowly. In general, the imaging results in time-domain imaging are better than those from the frequency-domain imaging, which not only is suitable for the qualitative detection of defects but also has great potential and application prospects in quantitative detection. This work shows an important guide for the application of THz technology to detect the composite material defects in civil aircraft.